The Effect of COVID-19 Pandemic on Foreign Body Aspiration - Ozturk, Kubra; Boybeyi, Ozlem; Soyer, Tutku (The Thoracic and Cardiovascular Surgeon, 2023)
Background This article evaluates the effect of coronavirus disease 2019 (COVID-19) pandemic on clinical course and management of cases that underwent bronchoscopy for suspected foreign body aspiration (FBA) in children.Methods The patients who underwent bronchoscopy with a presumptive diagnosis of FBA between July 2018 and December 2021 were evaluated for demographic features, clinical findings, management details, and outcomes. Patients were divided in two groups: before pandemic (group A) and during pandemic (group B).Results In total 79 cases with a median age of 5 years (4–5) in group A (n = 47) and 3 years (2–3) in group B (n = 32) were included (p < 0.05). The witnessed aspiration was significantly higher in group B (90.6%) when compared to group A (53%) (p < 0.05). Admission time was less than 48 hours in 30 cases (64%) in group A and 23 cases (72%) in group B (p = 0.002). The intervention time was less than 24 hours in 30 cases (64%) in group A, 9 cases (28%) in group B (p = 0.002). Bronchoscopy was performed after COVID-19 polymerase chain reaction (PCR) testing in all cases in group B. The positive FBA rate was 38% (n = 18) in group A, and 59% (n = 19) in group B (p = 0.067).Conclusion During pandemics, bronchoscopy for FBA was performed in younger infants than before pandemic and witnessed aspiration was significantly more common in that period. The differences in age groups and symptoms may be explained by spending more time at home during pandemics. Waiting for the PCR test results causes delays in the intervention. However, this delay did not cause any respiratory distress.
Keywords: COVID-19; pandemic; bronchoscopy; foreign body aspiration